Legal Protection for Food Suppliers in Hardship in Semarang City - Satar, Abdul; Winjaya Laksana, Andri (Jurnal Hukum Khaira Ummah, 2025)
This study aims to analyze the legal protection for food supply entrepreneurs in Semarang City in facing difficult conditions caused by external factors such as changes in raw material prices, distribution disruptions, or natural disasters. This study uses a qualitative approach with a case study method to explore the challenges faced by entrepreneurs in managing these risks. The data was collected through in-depth interviews with entrepreneurs, legal practitioners, and local governments, and analyzed using qualitative descriptive analysis techniques. The results of the study show that although there are regulations designed to protect entrepreneurs, such as in the Civil Code and the Consumer Protection Law, their implementation is still limited. Small entrepreneurs often do not have a sufficient understanding of their legal rights and are unable to access affordable legal services. This study recommends increasing legal understanding among entrepreneurs and improving the legal aid system for the small business sector.